FLOOD PROTECTION GARAGE SYSTEM - MOHD NOR@ ABDULLAH, MOHO FARIZ IKRAM (Universiti Teknologi PETRONAS, 2008)
This project is focus on the development of a flood protection garage system (FPGS) in order to protect vehicle and other valuable things inside the garage from flooding water. When flood happens, the water level detector circuit inside the garage will sense the existence of water in the respective level of the sensor. This sensor will send signal to the microcontroller to control motor operation in order to drive the jack and lift up the garage floor. The floor of the garage can also be lower down when the water level inside the garage decreases. Meanwhile, the signal will also be sent to the receiver via radio frequency transmission to alert the car owner about the flooding. The sensor, microcontroller and the wireless transmission are the main components ofFPGS